2022
DOI: 10.1007/s00705-022-05470-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of SARS-CoV-2 neutralizing antibodies in Lebanon

Abstract: According to the Lebanese Ministry of Public Health, more than 1,053,000 cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection have been confirmed in Lebanon so far. The actual number of cases is likely to be higher. We conducted a serological study from October 2020 to April 2021 to estimate the prevalence of SARS-CoV-2 neutralizing antibodies and identify associated factors. Serum samples as well as demographic, health, and behavioral data were collected from 2,783 subjects. Sera we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This high infection rate in these cycles may explain in part the higher levels of NAbs rates in December 202010. Our estimate of the NAbs titers is higher than estimates described in Oman using the live serum neutralisation assay where 8.5-16.8% sera tested positive in October -December 2020 8 , but lower than those found between February–March 2021 (36% versus 83.7%). This peak began in January 2021 as the transmittable alpha variant began to circulate worldwide.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This high infection rate in these cycles may explain in part the higher levels of NAbs rates in December 202010. Our estimate of the NAbs titers is higher than estimates described in Oman using the live serum neutralisation assay where 8.5-16.8% sera tested positive in October -December 2020 8 , but lower than those found between February–March 2021 (36% versus 83.7%). This peak began in January 2021 as the transmittable alpha variant began to circulate worldwide.…”
Section: Discussioncontrasting
confidence: 75%
“…A high seroprevalence of asymptomatic SARS-CoV-2 infection in blood donors, young recruit's army personnel and in the sub-group of individuals with suspected ADs was found and almost one person over 7 had contact with the virus in a population (n=1870). Interestingly, these infected persons had NAbs less than 1:16, a titer which we consider very low as compared to that obtained in mild or severely infected individuals (NAbs more than: 32 for our positive controls or in patients who experienced severe dieseas 8 .…”
Section: Discussioncontrasting
confidence: 63%
“…[89] SARS-CoV-2 seroprevalence studies are important to estimate the burden of COVID-19 in a population and to understand the disease transmission dynamics, risk of infection as well as the future and the evolution of the pandemic [90]. While serosurveys are important to guide the public health response, unfortunately, few seroprevalence studies on anti-SARS-CoV-2 antibodies were performed in Lebanon with most of them using sera collected early during the pandemic [91][92][93]. The results of these studies showed a gradual increase in seropositivity from 2.7% (November 2020) to 84.8% (April 2021) [91,93].…”
Section: Epidemiologic and Genomic Surveillance Of Sars-cov-2mentioning
confidence: 99%
“…While serosurveys are important to guide the public health response, unfortunately, few seroprevalence studies on anti-SARS-CoV-2 antibodies were performed in Lebanon with most of them using sera collected early during the pandemic [91][92][93]. The results of these studies showed a gradual increase in seropositivity from 2.7% (November 2020) to 84.8% (April 2021) [91,93]. This increase was expected due to the unprecedented rise in the number of COVID-19 cases detected during the same period (Figure 1A).…”
Section: Epidemiologic and Genomic Surveillance Of Sars-cov-2mentioning
confidence: 99%
“…The study revealed that 58.95% of the study population showed neutralizing antibodies. Individuals who had to leave for work during the pandemic and lived in suburban areas that did not adhere to preventive measures suffered from higher positivity rates 16 . Another seroprevalence study was conducted in Egypt.…”
Section: Introductionmentioning
confidence: 99%